A casebook of ethical challenges in neuropsychology - Bush, Shane S., 1965- (Studies on neuropsychology, development, and cognition., 2005)
The American Psychological Association published a revision of the Ethical Principles of Psychologists and Code of Conduct in 2002. This text, a companion to the 2002 text Ethical Issues in Clinical Neuropsychology by Bush and Drexler, presents the reader with common ethical challenges in neuropsychology. This text examines the differences between the 1992 and 2002 APA Ethics Codes as they relate to neuropsychological activities. The authors present cases and discuss ethical issues related to neuropsychological practice with a variety of patient populations and in a variety of clini.